(untitled) (Research in Agriculture Livestock and Fisheries, 2016)
A study was conducted to investigate the infestations of monogenetic trematodes of juvenile carps of Mymensingh region. A total of eight (8) farms, four Government (Govt.) and four Private (Pvt.) fish farms were investigated of Indian major carps - Catla (Catla catla), Rui (Labeo rohita) and Mrigal (Cirrhinus cirrhosus) during June, 2010 to May, 2012. Monthly samplings were carried out with 5 fishes of each species and each farm. Altogether 2880 fish host were examined of which 1424 hosts were found to be infested with monogenetic trematodes of which 626 from Govt. and 798 from Pvt. farms. The monogeneans were very common in gills of all fishes. Water quality parameters were taken and management practices were also noted. The risk of infestation by monogeneans of carp significantly (p<0.001) increased when the water quality parameters were deteriorated. Prevalence (%), mean intensity and abundance were found to be species specific and also varied with seasons and management systems practiced by different farmers. Prevalence (%) of monogeneans in carps was significantly (p< 0.001) higher in Pvt. farm than that of Govt. farms. The prevalence (%) of monogeneans were significantly (p< 0.01) higher in rainy season than dry season. Mrigal was more infected by monogeneans followed by Catla and Rui. Res. Agric., Livest. Fish.3(1): 187-194, April 2016